Structure of the binding site for nonnucleoside inhibitors of the reverse transcriptase of human immunodeficiency virus type 1. - Smerdon, S J (1994)
The dipyridodiazepinone Nevirapine is a potent and highly specific inhibitor of the reverse transcriptase (RT) from human immunodeficiency virus type 1 (HIV-1). It is a member of an important class of nonnucleoside drugs that appear to share part or all of the same binding site on the enzyme but are susceptible to a variety of spontaneous drug-resistance mutations. The co-crystal-structure of HIV-1 RT and Nevirapine has been solved previously at 3.5-A resolution and now is partially refined against data extending to 2.9-A spacing. The drug is bound in a hydrophobic pocket and in contact with some 38 protein atoms from the p66 palm and thumb subdomains. Most, but not all, nonnucleoside drug-resistance mutations map to residues in close contact with Nevirapine. The major effects of these mutations are to introduce steric clashes with the drug molecule or to remove favorable protein-drug contacts. Additionally, four residues (Phe-227, Trp-229, Leu-234, and Tyr-319) in contact with Nevirapine have not been selected as sites of drug-resistance mutations, implying that there may be limitations on the number and types of resistance mutations that yield viable virus. Strategies of inhibitor design that target interactions with these conserved residues may yield drugs that are less vulnerable to escape mutations.